Assessment of Long‐Term Use Versus Discontinuation of Direct Oral Anticoagulant After Catheter Ablation for Atrial Fibrillation—RYOUMA Registry Subanalysis - Yuka Oda; Akihiko Nogami; Yuki Komatsu; Kyoko Soejima; Itsuro Morishima; Kenichi Hiroshima; Ritsushi Kato; Satoru Sakagami; Fumiharu Miura; Keisuke Okawa; Masayuki Fukuzawa; Atsushi Takita; et al. (Annals of Noninvasive Electrocardiology)
ABSTRACT Background The relationship between oral anticoagulant (OAC) status after catheter ablation (CA) for atrial fibrillation (AF) and the risks of ischemic stroke or major bleeding events is still unknown. Methods This is a subanalysis of the RYOUMA registry, a prospective multicenter observational study of Japanese patients who underwent CA for AF in 2017–2018. Results Of the 2844 patients, the rate of DOAC continuation was 48.1%, 69.6%, and 80.9% in patients with a CHADS2 score of 0–1, 2, and 3–6, respectively. Among the patients taking DOACs with a CHADS2 score of 0–1 and 2, the incidence rates of major bleeding were significantly higher than those of ischemic stroke or systemic embolic events (SEEs) (1.3%/year [95% CI, 0.6–2.1] vs. 0.3%/year [95% CI, 0.0–0.7], p = 0.019; 1.8%/year [95% CI, 0.6–3.0] vs. 0.2%/year [95% CI, 0.0–0.6], p = 0.018, respectively). However, there was no difference between the incidence rates of major bleeding events and ischemic stroke or SEEs in patients taking DOACs with a CHADS2 score of 3–6 (1.6%/year [95% CI, 0.2–3.0] vs. 1.0%/year [95% CI, 0.0–2.1], p = 0.474). Conclusions In patients with a CHADS2 score of 2, those who continued taking DOACs had a higher incidence rate of major bleeding events compared to ischemic stroke/SEEs, similar to those with a CHADS2 score of 0–1. Conversely, in patients with a CHADS2 score of 3–6, the incidence rates of both ischemic stroke/SEEs and major bleeding were similarly high. Trial Registration: The study was registered as UMIN000026092 (University Hospital Medical Information Network‐Clinical Trial Registry)